2023
DOI: 10.3389/fimmu.2023.1114348
|View full text |Cite
|
Sign up to set email alerts
|

The intestine: A highly dynamic microenvironment for IgA plasma cells

Abstract: To achieve longevity, IgA plasma cells require a sophisticated anatomical microenvironment that provides cytokines, cell-cell contacts, and nutrients as well as metabolites. The intestinal epithelium harbors cells with distinct functions and represents an important defense line. Anti-microbial peptide-producing paneth cells, mucus-secreting goblet cells and antigen-transporting microfold (M) cells cooperate to build a protective barrier against pathogens. In addition, intestinal epithelial cells are instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 214 publications
(234 reference statements)
0
10
0
Order By: Relevance
“…The intestine is the organ that is most susceptible to antigens and microorganisms, which makes it a crucial line of defense to fight against pathogenic microorganisms. 39 Detrimental environments can cause the oxidation and inflammation of the intestine, and numerous studies have indicated that CTX can induce a shortening and shedding of the intestinal villus, ultimately leading to damage of the intestinal mucosal layer. 32,33,40 Our current research suggested that CTX triggered damage to the jejunum structure, as manifested by the disappearance of muscle layers and exposure of the lamina propria structure; however, supplementation with BCL restored the structures of the jejunal epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The intestine is the organ that is most susceptible to antigens and microorganisms, which makes it a crucial line of defense to fight against pathogenic microorganisms. 39 Detrimental environments can cause the oxidation and inflammation of the intestine, and numerous studies have indicated that CTX can induce a shortening and shedding of the intestinal villus, ultimately leading to damage of the intestinal mucosal layer. 32,33,40 Our current research suggested that CTX triggered damage to the jejunum structure, as manifested by the disappearance of muscle layers and exposure of the lamina propria structure; however, supplementation with BCL restored the structures of the jejunal epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We observed an increased abundance of Bacteroidetes and Verrucomicrobia , and depletion of Firmicutes in the feces of chronic morphine‐treated mice. The intestinal epithelium restricts bacteria from colonizing the intestine tissue and entering systemic circulation through multiple contingencies that maintain homeostasis between the intestinal epithelium and the gut bacteria 19,21,39 . One mechanism is the secretion of AMPs into the intestinal lumen by enterocytes and crypt Paneth cells 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma cells residing in the intestinal lamina propria secrete immunoglobulin A (IgA). The secreted IgA reaches the polymeric immunoglobulin receptor (pIgR) on intestinal epithelium via simple diffusion for transcytosis into the intestinal lumen, where IgA assures the homeostasis of microbiome and protects the host against enteric infections ( 65 67 ).…”
Section: Overview Of Ibd and Circrnasmentioning
confidence: 99%